History of Sumba Ikat Weaving: Reflection of Sumba’s Cultural Identity Towards Creative Industry - Krisnadi, Tasya Widya (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This literature review aims to analyse the transformation of Sumba ikat weaving from an ancestral tradition into part of the creative industry that contributes to the local economy and tourism. The research method used is the historical method, namely heuristics, criticism, auffassung, and darstellung and through a systematic literature review of various scientific sources related to Sumba ikat weaving. The results of the study show that the history of Sumba ikat weaving is rooted in the natural wealth and traditional values of the local community, with motifs that have symbolic meanings in social and spiritual life. The transformation of Sumba ikat weaving from tradition to creative industry is marked by the evolution of production techniques, design innovation, and product diversification, despite facing challenges in maintaining the sustainability of natural resources and quality standardisation. The socio-cultural impact of this transformation is seen in the shift in function from the role of customary rituals to commercial products, which affects gender dynamics and the cultural identity of the Sumbanese people. In the global context, Sumba ikat weaving is increasingly integrated into the global supply chain, facing competition with global fashion products while maintaining its uniqueness and authenticity. Ecofeminism and local community empowerment approaches are key in maintaining a balance between cultural values and market demands.